Penyusunan Kumpulan Cerkak Bebungahing Rekasa Sebagai Sumber Belajar untuk Jenjang SMP/MTs - Cahyani, Ananda Pramesti Regitha; Zahro', Azizatuz (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Cerkak is one of the Javanese language learning materials that is less attractive to students because of the lack of interesting learning resources. This research and development aims to produce a collection of short stories entitled Bebungahing Rekasa as a learning resource for the SMP/MTs level. This study uses the Borg and Gall model which consists of 10 stages, namely (1) needs analysis and data collection, (2) planning, (3) product design development, (4) validation test, (5) initial product revision, (6) limited field tests, (7) product revisions, (8) field tests, (9) final product improvements, and (10) socialization and implementation. Data were obtained from material expert validation tests, practical tests from Javanese language teachers, and field tests on 30 class VIII F students of SMP Negeri 18 Malang. The resulting collection of cerkak contains 12 titles with various themes, and raises the values of Javanese culture and character education. Based on the results of the validation and testing of practitioners, it was found that the eligibility percentage was 87% from material experts and 75% from practitioners. Based on the results of the field test, the 12 cerkak titles received a good response even though there were some words that the students did not understand. The test results show that the Bebungahing Rekasa cerkak collection can be used as a source of learning Javanese, especially for class VIII at the SMP/MTs level, also can add to regional reading materials for the general public.